Reproductive toxicity of seafood contaminants: Prospective comparisons of Swedish east and west coast fishermen's families - Rignell-Hydbom Anna; Rylander Lars; Axmon Anna (BMC, 2008)
Abstract Cohorts comprising fishermen's families on the east coast of Sweden have been found to have a high consumption of contaminated fish as well as high body burdens of persistent organochlorine pollutants (POPs). Their west coast correspondents are socio-economically similar, but with considerably lower POP exposure since the fish caught on the west coast is far less contaminated. The rationale for this was that the cohorts residing on the east coast of Sweden have been found to have a high consumption of contaminated fish as well as high body burdens of POPs, whereas their west coast correspondents are socio-economically similar, but with considerably lower POP exposure since the fish caught on the west coast is far less contaminated. Among the reproductive outcomes investigated are included both male and female parameters, as well as couple fertility and effects on the fetus. A range of exposure measures, including both questionnaire assessments of fish consumption and biomarkers, have been used. The most consistent findings of the studies are those related to the fetus, where a decreased birth weight was found across all measures of exposure, which is in agreement with studies from other populations. Some markers for male reproduction function, i.e. sperm motility, sperm chromatin integrity, and Y:X chromosome ratio, were associated with POP exposure, whereas others, such as sperm concentration and semen volume, were not. With respect to couple fertility and female reproductive parameters, no support was given for associations with POP exposure. Although some associations may have been affected by beneficial effects of essential nutrients in seafood, the overall findings are meaningful in the context of reproductive toxicity and support the usefulness of the epidemiological design.